NILAI MORAL PASENG DALAM SASTRA LISAN BUGIS PAGATAN - Faisal Batennie, David Hariyanto, Muhammad Nauval Pattiroi (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2025)
The OPMA XIV community service program held in Sekapung Village aims to strengthen the role of university students in community development through a cross-sector collaborative approach. The program consists of five main activities: reproductive health education in collaboration with Sungai Bali Public Health Center, coastal cleanup with TNI personnel and local residents, drug abuse prevention counseling with the Sungai Bali Police Sector, recycled craft training with the local PKK women’s group, and teaching programs at three local schools. These activities were designed to address community needs in health, education, environmental awareness, and creative economic empowerment. The outcomes indicate an increase in health literacy, environmental awareness, community cooperation, productive skills, and student learning motivation. Collaboration between community elements was key to the success of the program. To ensure sustainability, it is recommended that local institutions be further involved, follow-up training be conducted, and the outcomes be documented as a replicable model. Thus, OPMA XIV not only serves as a platform for student service, but also as a driving force for social transformation in Sekapung Village